Pendidikan Agama Islam dalam Bingkai Filfasat: Studi Analisis Aliran Religius Konservatif (Al-Dini), Aliran Religius Rasional (Al Muhafid), dan Aliran Pragmatis Instrumental - Wasik; Mat Sari; Hamim Dzulqarnain Sofa (Jurnal Pendidikan Islam, 2022)
Current developments that continue to advance force us to develop Islamic educational theories in the learning process. In the philosophy of Islamic religious education, there are three main streams, namely the conservative religious, rational religious, and instrumental pragmatic schools. This article examines the study of the theory of Islamic religious education through this school, with the main figures from the three streams above, namely using a library research to find data from several sources and literature which is prioritized implicitly and specifically. The results of the study show that a philosophical approach produces several aspects, starting from the concept of teaching and learning. The process of learning from psychological foundations, namely the methods used must be equally active in fighting for both individually and in groups. From these main streams, the first is a conservative religious school which is only applied in the environment of Islamic religious teachings, which was pioneered by Imam Ghazali, then Al-Aqliy or Rational Religious Akhwa Al-Shofa, who is the main character, believes that all learning in scientific disciplines is very important. it is important to adhere to and study it, then finally the flow pioneered by Ibnu Kholdun, namely the instrumental pragmatic school which holds that education is not only limited to ukhrowi between worldly and ukhrowi must be fought for and studied in depth, through Islamic education everything can be obtained optimally.